POTENSI DAN SEBARAN IKAN TERUBUK (Tenualosa macrura) DI PERAIRAN PROPINSI RIAU - Muchlizar Muchlizar; Tengku Dahril; Deni Efizon (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This research was conducted on April to November 2015 in the and continued until September 2016. This study aims to determine the purpose of this study is to obtain a picture of population dynamics and distribution of fish Terubuk (T. macrura) based on data and information about: population density, gender ratio, size and growth, spatial distribution / spatial distribution And ruaya / Migration Fish in the waters of Bengkalis Regency. This research uses survey method, where fish terubuk serve as the object of research while Fishing Fishing Terubuk in waters of Bengkalis Province Riau Province as a place of research. That includes three districts namely Bengkalis District, Bukit Batu and Siak Kecil. Acoustic data is processed using SONAR ver.4 software. Based on research results the potential value of fish stock (pias) and terubuk female (terebas) is 26.9 tons / year, with the stock density reaches 17.2 kg / km2. The spawning areas are in the vicinity of Lalang Strait and P.Padang Strait until encountered by Bengkalis Strait in the peak phase of the bright moon and the peak of the dark moon. Survey results indicate that migration or outrageous fish ruaya not only affect spawning factors but there are other important factors namely growth and sex transfer factors, where pale fish will always be in deep strait deepwater (Terubuk Fish Sanctuary Area / Zone 1 -6). Long-term distribution of long-term fish does not indicate a shift in the capital progression, such as long frequency data, but only fish (pias), female fish (transplant), and transitional sex fish; Where the 'Pias' group is 20 cm below; Category 'Terubuk' size 20 cm and above.